Characteristic of bio-geometric profile of students’ posture and physical fitness in process of physical education - M.V. Dudko (Physical Education of Students, 2015)
Purpose: to determine specific features of bio-geometric profile of posture and physical fitness of students in process of physical education. Material: 250 students were tested. Video-recording and analysis of bio-geometric profile of human posture were fulfilled. Program Torso was used for this purpose. Results: it was found out that only 15.2% of students had correct posture. The most quantity of posture abnormalities was detected in 36.4% of the tested. In sagittal plane we observed the following types of abnormalities: round back - in 24.4% of students, slouching back - in 24% of students. We found that 63.3% of students with normal posture are in zone of risk. Low backbone flexibility, mobility of hip joints and elasticity of hamstrings was detected on students. Conclusions: students with unsatisfactory bio-geometric profile of posture (scoliosis posture - 43.33%; round back - 23. 33%; slouching back - 22. 73%) are in the called pre-morbid state of muscular-skeletal apparatus.